Study of Agri-Clinics & Agri-Business Centres for Improving Women Farmers' Access to Extension Services in Agriculture - Rani Nidhi , Masih Jolly and Shruthi Gadhe, (Indian Journal of Extension Education, 2017)
Women experience number of constraints to access extension services and other facilities like seed, water, credit,subsidy etc. The government of India started Agri-Clinics & Agri-Business Centres in 2002 to promote farmgraduates as entrepreneurs in agriculture and allied fields like poultry, fisheries, livestock etc. This study aimed toascertain the impact of Agri-Clinics & Agri-Business Centres in 6 states of India namely Punjab, Assam, Tamil Nadu,Maharashtra, Karnataka and Bihar. Findings indicated that success rate was maximum in Maharashtra followed byPunjab and Tamil Nadu. Lack of government and bank support could not ensure much success in Bihar while womengraduates evinced keen interest on salaried jobs in Karnataka.